Long‐Lasting Geomagnetically Induced Currents and Harmonic Distortion Observed in New Zealand During the 7–8 September 2017 Disturbed Period. Issue 6 (19th June 2018) - Clilverd, Mark A.; Rodger, Craig J.; Brundell, James B.; Dalzell, Michael; Martin, Ian; Mac Manus, Daniel H.; Thomson, Neil R.; Petersen, Tanja; Obana, Yuki
Abstract: Several periods of geomagnetically induced currents (GICs) were detected in the Halfway Bush substation in Dunedin, South Island, New Zealand, as a result of intense geomagnetic storm activity during 6 to 9 September 2017. Unprecedented data coverage from a unique combination of instrumentation is analyzed, that is, measurements of GIC on the single‐phase bank transformer T4 located within the substation, nearby magnetic field perturbation measurements, very low frequency (VLF) wideband measurements detecting the presence of power system harmonics, and high‐voltage harmonic distortion measurements. Two solar wind shocks occurred within 25 hr, generating four distinct periods of GIC. Two of the GIC events were associated with the arrival of the shocks themselves. These generated large but short‐lived GIC effects that resulted in no observable harmonic generation. Nearby and more distant magnetometers showed good agreement in measuring these global‐scale magnetic field perturbations. However, two subsequent longer‐lasting GIC periods, up to 30 min in duration, generated harmonics detected by the VLF receiver systems, when GIC levels continuously exceeded 15 A in T4. Nearby and more distant magnetometers showed differences in their measurements of the magnetic field perturbations at these times, suggesting the influence of small‐scale ionospheric current structures close to Dunedin. VLF receiver systems picked up harmonics from the substation, up to the 30th harmonic, consistent with observed high‐voltage increases in even harmonic distortion, along with small decreases in odd harmonic distortion. Key Points: Analysis of a transformer in New Zealand shows a sequence of large geomagnetically induced currents (GIC) associated with a storm period Unique combination of measurements show primarily even harmonics generated by transformer saturation when GIC > 15 A During study period only longer‐lasting GIC generated observable harmonics but limited GIC impact from impulsive solar wind shock events